Grave sight ebook - Harris, Charlaine (Harper Connelly, 2005)
The first Harper Connelly mystery from #1 New York Times bestselling author Charlaine Harris! Harper Connelly has what you might call a strange job: she finds dead people. She can sense the final location of a person who’s passed, and share their very last moment. Harper and her stepbrother Tolliver are experts at getting in, getting paid, and then getting out of town fast—because the people who hire Harper have a funny habit of not really wanting to know what she has to tell them. At first, the little Ozarks town of Sarne seems like no exception.  A teenage girl has gone missing, but the secrets of her death—and the secrets of the town—are deep enough that even Harper’s special ability can’t uncover them.  With hostility welling up all around them, she and Tolliver would like nothing better than to be on their way.  But then another woman is murdered.  And the killer’s not finished yet...